OC-062 Low Incidence of Aspiration Events during Home Nasogastric Feeding: A Safe Strategy for Long Term Feeding?. (4th June 2013) - Mohamed, O; Stapely, C; Gunston, H; Gregory, L; Smith, L; Rogers, S; Clark, J; Pratt, J; Trebble, T M; Pearl, D S
Abstract : Introduction: Nasogastric (NG) pump feeding is associated with risks of aspiration and subsequent pneumonia with previous studies in adult inpatients suggesting 2.4 aspiration episodes per 1000 tube-feeding days. However, there is little published data on outcomes of patients receiving home NG feeding. We analysed our long term home NG feeding cohort for evidence of aspiration related hospital admission. Methods: This was a retrospective service evaluation of the home enteral tube feeding cohort at Portsmouth Hospitals NHS Trust. Data was obtained from hospital electronic databases, patient clinical notes and PAS patient management software. Data was analysed in SPSS 20. Results: A total of 117 patients who had received home NG feeding over previous 5 years were evaluated. 30 patients (26%) were excluded due to incomplete datasets. 87 patients were recruited (Male [48%], Female [52%], age [mean 55.6; 95% confidence interval 51.8–59.2]) with a total of 12957 tube-feeding days (mean 150; 95% confidence interval 110–191 days). Indications include upper aerodigestive tract cancer, 32; malnutrition, 25; neurodegenerative disorders, 6; connective tissue disorders, 2; stroke, 1; lymphoma, 1; metabolic stabilisation of short bowel and or high output stoma, 16. Eight hospital admissions in separate patients were recorded; however, only 1 episode of pneumonia was recorded (0.08 aspiration episodes per 1000 tube-feeding days). There were no hospital admissions relating to misplaced/displaced NG tubes. Conclusion: Home NG pump feeding represents a safe long-term alternative to gastrostomy feeding when supported by a robust specialist enteral tube feeding support service (ETFSS), in those deemed unsuitable for gastrostomy placement. A 30-fold lower incidence of aspiration episodes compared with published inpatient literature (0.08 vs. 2.4 episodes/1000 tube feeding days) reflects expertise of clinical nutrition nurse specialists within the ETFSS, with appropriate patient selection and outreach management. A daytime walk in service prevents unplanned hospital admissions through tube displacement. Disclosure of Interest: None Declared